(untitled) (Journal of Mechanical Engineering, 2010)
After the discovery, carbon nanotubes (CNTs) have received tremendous scientific and industrial interests. This is due to their exceptional mechanical, electrical, and thermal properties. CNTs having pristine structure (i.e., structure without any defect) hold very high mechanical properties. In this article, mechanical properties of CNTs are studied under both tensile and compressive loads using molecular dynamics (MD) simulations. Four armchair single-walled nanotubes (SWNTs) having indexes of (3,3), (4,4), (5,5) and (6,6) with pristine structure are simulated with MD. Molecular simulations are carried out using the classical MD method, in which the Newtonian equations of motion are solved numerically for a set of atoms. The velocity- Verlet algorithm is used for solving the Newtonian equations of motion. The Brenner potential is used for carbon-carbon interaction in the CNT and temperature of the system is controlled by velocity scaling. Simulation results show that modulus of elasticity of CNTs varies significantly with CNT diameter. The results obtained from the compressive test by MD simulations are in well agreement with the results obtained from theoretical Euler equation and parabolic equation for long and short column respectively. Keywords: Carbon nanotubes; Molecular dynamics; Young’s modulus; Failure strength; Failure strain. DOI: 10.3329/jme.v40i2.5346 Journal of Mechanical Engineering, Vol. ME 40, No. 2, December 2009 72-78